John C. McCombs, Charter of the City of Allegheny, at 141, City Ordinances, Fire Arms, Fire and Squibs, § 1 (1870) - (:unkn) unknown (My University, 1870)
Any person who shall fire off, or discharge any gun, pistol, fowling piece, or other fire-arms, within the limits of the city of Allegheny, unless the same be in defense of person or property, shall forfeit and pay a fine of not less than $1.00 nor more than $4.00, upon conviction.]
Keywords: DISCHARGE